PENGEMBANGAN APLIKASI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN UNTUK MENGENAL TATA SURYA PADA SD ISLAMIC VILLAGE - Edi Junaedi; Adiyati, Nita; Wulandari, Fithri; Maulana Ramadhan, Adrian (NUANSA INFORMATIKA, 2023)
Educators must adapt their teaching methods during the COVID-19 pandemic to ensure effective and captivating learning experiences that incorporate interactivity, challenges, motivation, and allow students to nurture their creativity and independence based on their individual talents and interests. At Islamic Village Elementary School, it is especially important to utilize engaging learning media since elementary students have a natural enthusiasm for new concepts. When selecting learning media, factors such as learning objectives, effectiveness, user-friendliness, and flexibility should be taken into consideration. Augmented Reality (AR) applications have emerged as an exciting advancement in learning media, particularly in helping students comprehend Natural Science subjects. Thus, an AR application has been developed as a learning tool for Natural Science at Islamic Village Elementary School, utilizing the Marker-Based Tracking AR method. The research aims to facilitate students' learning and understanding of the material while making the learning process more captivating and less monotonous. Within the application, objects are visually presented in 3D using animations, sound, and appealing colors. The research methodology encompasses literature review, field study, and sample calculations. The outcome of this research is a mobile application that serves as a supportive tool to enhance the learning experience.